Polymer-derived ceramic molten metal filters - Semerci, Tugce; Dizdar, Kerem Can; Kulkarni, Apoorv; Dispinar, Derya; Soraru, Gian Domenico; Vakifahmetoglu, Cekdar (Springer Science and Business Media LLC, 2022)
This paper reports the synthesis and the performance of polymer-derived ceramic filters for molten metal filtration. Two different filter types were studied: foam filters produced from flexible polyurethane (PU) foams and additive manufacturing (AM) filters produced from thermoplastic polyurethane (TPU) cellular structure, and the results from all filter types were compared with that of the commercially used SiC foam filters. In both cases, the urethane-based polymeric template was impregnated with the preceramic solution, followed by pyrolysis. The produced ceramic components were then used to filter a molten Al alloy (A357), and the resulting Al samples were characterized for their mechanical properties. When filters were used, more reproducible and reliable mechanical properties were achieved compared to the samples obtained without any filtration. Among the different filters tested, the foam filters demonstrated better performance in comparison with the AM ceramic filters due probably to the three-dimensional interconnected porosity compared with the unidirectional cellular structure of the AM ceramic filters.[GRAPHICS].

This paper reports the synthesis and the performance of polymer-derived ceramic filters for molten metal filtration. Two different filter types were studied: foam filters produced from flexible polyurethane (PU) foams and additive manufacturing (AM) filters produced from thermoplastic polyurethane (TPU) cellular structure, and the results from all filter types were compared with that of the commercially used SiC foam filters. In both cases, the urethane-based polymeric template was impregnated with the preceramic solution, followed by pyrolysis. The produced ceramic components were then used to filter a molten Al alloy (A357), and the resulting Al samples were characterized for their mechanical properties. When filters were used, more reproducible and reliable mechanical properties were achieved compared to the samples obtained without any filtration. Among the different filters tested, the foam filters demonstrated better performance in comparison with the AM ceramic filters due proba...
Keywords: Polymer derived ceramics, 3D printing, Molten metal filters